POETRY OF IQBOL MIRZO’S POEMS - Anarkulova Zubayda Fayzullo qizi; Mahliyo Ahmadqulova Anvar qizi (Web of Journals Publishing, 2025)
This article provides an analysis of the issues raised in the poems of the People's Poet of Uzbekistan Iqbol Mirzo. The poet's poems are full of love for the motherland and an analytical approach to his poems on a number of topics. This article analyzes the main thematic and artistic features of Iqbol Mirzo’s poetry, one of the leading representatives of modern Uzbek literature. The study highlights the diversity, sincerity, and philosophical depth of the poet’s works. Through an examination of his poems such as “Tell Me, My Friend, What Have We Done for Our Homeland?”, “What Is Happiness?”, “What They Call Love”, and “Awakening”, the article explores how the poet expresses feelings of patriotism, love, and human emotion in simple yet profound language. It is observed that Iqbol Mirzo skillfully employs artistic devices such as metaphor, simile, and hyperbole to enhance the emotional and aesthetic impact of his poetry. His verses are characterized by sincerity, lyricism, and a deep sense of reflection, which make them appealing to a wide readership. The article concludes that Iqbol Mirzo’s poetry not only reflects the beauty of the Uzbek language and national spirit but also conveys universal human values through artistic expression.
Keywords: Poetry, analysis, artistic word, mental concept, psyche, sing, poem.